Les industries de quincaillerie et de ferronnerie décorative dans la région de Tinchebray (Orne) : histoire d'un pôle industriel rural - Monique Le Chêne (In Situ)
Ironmongery and decorative metalwork today occupy more than six hundred workers in eleven firms scattered across an area of about five kilometres around the village of Tinchebray in the Orne department. This activity may be seen as the legacy of older forms of industrial production, located in this rural environment far from important industrial centres. The firms at Tinchebray have developed strong links in which competition and inter-dependence are mingled. Presented in the form of a chronicle, this article traces the evolution of these industries and of their relations to the local context. The industrial system it describes is a complex one, drawing from this local context the strengths that have enabled it to confront the economic upheavals of the 20th century. The article also underlines a paradox which has become apparent over the last decade, contrasting the outward-looking economic logics of the firms themselves and the attitude of the local authorities, looking inwards and according considerable importance to the locality for economic development and social synergy.